Acetylene Reduction by Symbiosomes and Free Bacteroids from Broad Bean (Vicia faba L.) Nodules (Role of Oxalate). - Trinchant, J. C. (1994)
We report the presence of oxalate in the organic acid fraction of broad bean (Vicia faba L.) nodule cytosol. Using both high-performance liquid chromatography and enzymic assays, high levels of oxalate were detected (70.4 [plus or minus] 2.4 mM). To study the potential role of oxalate as an energy-yielding substrate for nitrogenase activity, free bacteroids were isolated from nodules and found to oxidize oxalate in support of C2H2 reduction under O2 tensions that were lower than those required to oxidize succinate, another dicarboxylate commonly detected in legume nodules. Symbiosomes of broad bean, isolated for the first time from amide-producing nodules, were provided with [14C]oxalate and found to have uptake kinetics with a lower affinity [Km(oxalate) = 330 [mu]M] than that for free bacteroids [Km(oxalate) = 130 [mu]M]. In anaerobic preparations of symbiosomes supplied with purified oxyleghemoglobin, O2 consumption was stimulated by oxalate from 20.2 [plus or minus] 0.8 nmol O2 min-1mg-1 protein to 24.5 [plus or minus] 1.1 nmol O2 min-1 mg-1 protein but always remained lower than the rate of O2 consumption in free bacteroids (32.2 [plus or minus] 1.4 nmol O2 min-1 mg-1 protein). Under these conditions, C2H2 reduction activity was 9.7 [plus or minus] 0.8 and 15.1 [plus or minus] 0.9 nmol C2H4 min-1 mg-1 protein for symbiosomes and bacteroids, respectively. These data support the suggestion that oxalate may play a role as a carbon substrate in support of N2 fixation in broad bean nodules.